Guidelines on patentability and access to medicines - Germán Velásquez (South Centre, 2015)
Until recently, the link between the examination of patents carried out by national patent offices and the right of citizens to access to medicines was not at all clear. They were two functions or responsibilities of the State that apparently had nothing to do with each other. Examining the growing literature on intellectual property and access to medicines, it seems that the analysis of one actor has been left out: the patent offices. And the reason is clear: patent offices are administrative institutions. Patentability requirements are not defined by patent offices, but frequently by the courts, tribunals, legislation or treaty negotiators. There is now greater understanding that the examination of patents and the role played by patent examiners are key elements that could contribute to or obstruct access to medicines. Given the impact of pharmaceutical patents on access to medicines, patent offices should draw up public policies and strategies that respond to national health and medicine policies.
Keywords: 300; Immaterialgüterrechte; Arzneimittel; Internationales Patentrecht; TRIPS; Welt